The Impact of Parental Involvement on Student Writing Ability: A Meta-Analysis - Hongli Yang; Ying Chen (MDPI AG, 2023)
The impact of parental involvement on student academic achievement has been confirmed by many studies. However, researchers differ on whether parental involvement can statistically improve student writing skills. Furthermore, the association between parental intervention duration and student writing ability is unclear. Consequently, this study examines the impact of parental involvement on student writing ability through a meta-analysis of 13 studies conducted between 1996 and 2021, with effect sizes of 117 and 1449 participants. Three main findings in the meta-analysis results werek identified. First, the overall effect of parent writing participation on student writing ability was statistically significant, resulting in a moderate positive effect (g = 0.666 95% CI [0.324, 1.008]), p < 0.001). Second, parental participation behavior methods and student educational stages had no significant impact on student writing ability. Third, differences in school area and parental intervention duration had a significant impact on student writing ability, suggesting that parental involvement has a greater role in promoting an improvement in student writing ability in urban schools, and that long-term intervention is more conducive to improving student writing ability.